'Blood and water flowed to the ground': sacred topography, biblical landscapes and conceptions of space in the Libellus de expugnatione Terrae Sanctae per Saladinum. Issue 3 (27th May 2021) - Kane, James H.
ABSTRACT: The anonymous Latin eyewitness account of Ṣalāḥ al-Dīn's conquest of the kingdom of Jerusalem in 1187, known as the Libellus de expugnatione Terrae Sanctae per Saladinum, is fundamentally preoccupied with the capture and destruction of Christian holy sites in the Levant. This article analyses conceptions of space in the Libellus with a particular focus on the author's exegetical approach to the sacred topography of the Holy Land, which arguably plays a larger role in the narrative than the historical actors themselves. It examines how the author deploys this landscape typologically in order to tie the events of 1187 into the conceptual framework of the biblical past. The paper also explores how his positioning of Christians and Muslims within the spaces of the text highlights the weaknesses of the former and the dual nature of the latter as both desecrators and potential worshippers in this region of conflict and encounter.